Kinematic evolution of kilometre-scale fold trains in surge-type glaciers explored with a numerical model. (August 2022) - Young, Erik M.; Flowers, Gwenn E.; Jiskoot, Hester; Gibson, H Daniel
Abstract: Glacier surging provides a window into the processes responsible for some of the fastest ice flow on Earth. Surge-type glaciers are festooned with fold trains—many visible from space—which encode the history of polyphase deformation associated with this form of episodic fast flow. We conduct the first investigation of the kinematic evolution of these kilometre-scale folds using a full-Stokes numerical ice-flow model. We model the folds through multiple surge cycles within a set of synthetic glacier confluence configurations, and identify how differences in glacier flow regimes imprint themselves on three-dimensional fold geometry. Based on simulation results across parameter space, we present an archetype of kinematic evolution that describes the transition from cylindrical vertically plunging gentle folds emplaced during the surge phase, to complex depth-varying folds following multiple cycles of surging and quiescent flow. A detailed examination of the surface trace of these folds highlights the links between glacier flow regime and folding. The initial fold geometry is controlled by longitudinal and lateral shear stress regimes during surging, while fold evolution is governed primarily by lateral shearing after emplacement. This reflects the influence of valley geometry and glacier dynamics on the variability of flow regimes during both surging and quiescent flow. Finally, we illustrate the potential of our approach to reconstruct more complex fold geometries as observed in nature. Graphical abstract: Image 1 Highlights: We simulate surge-like glacier behaviour using the numerical ice-flow model Elmer/Ice. 3-D kinematic evolution of folding is then characterised across multiple phases of deformation. We determine the sensitivity of fold geometry to glacier geometry, dynamics, and mass balance. The model qualitatively reproduces key characteristics of observed folds.